A comparison of caffeine versus pseudoephedrine on cycling time-trial performance - Spence, A.; Sim, M.; Landers, G.; Peeling, P. (International Journal of Sport Nutrition and Exercise Metabolism, 2013)
Both caffeine (CAF) and pseudoephedrine (PSE) are proposed to be central nervous system stimulants. However, during competition, CAF is a permitted substance, whereas PSE is a banned substance at urinary levels >150 µg·ml-1. As a result, this study aimed to compare the effect of CAF versus PSE use on cycling time trial (TT) performance to explore whether the legal stimulant was any less ergogenic than the banned substance. Here, 10 well-trained male cyclists or triathletes were recruited for participation. All athletes were required to attend the laboratory on four separate occasions—including a familiarization trial and three experimental trials, which required participants to complete a simulated 40 km (1,200 kJ) cycling TT after the ingestion of either 200 mg CAF, 180 mg PSE or a nonnutritive placebo (PLA). The results showed that the total time taken and the mean power produced during each TT was not significantly different (p > .05) between trials, despite a 1.3% faster overall time (~57 s) after CAF consumption. Interestingly, the time taken to complete the second half of the TT was significantly faster (p < .05) in CAF as compared with PSE (by 99 s), with magnitude based inferences suggesting a 91% beneficial effect of CAF during the second half of the TT. This investigation further confirms the ergogenic benefits of CAF use during TT performances and further suggests this legal CNS stimulant has a better influence than a supra-therapeutic dose of PSE.